2012
DOI: 10.1111/j.1365-2702.2012.04207.x
|View full text |Cite
|
Sign up to set email alerts
|

Caring to achieve the maximum independence possible: a synthesis of qualitative evidence on older adults’ adaptation to dependency

Abstract: The findings show the interconnected nature of physical, material, social and emotional aspects of care; and the profound social impact of providing and receiving care. Relevance to clinical practice.  The nurses can assist families and older adults to enhance adaptation to dependency, anticipating and helping to redefine the concepts of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 48 publications
1
23
0
4
Order By: Relevance
“…After agreeing the seven inclusion criteria, a further 48 qualitative reviews were then identified from DARE and assessed. At this stage, 15 [ 20 34 ] were excluded as they failed one or more of the criteria, leaving us with 33 reviews [ 11 , 35 47 , 48 66 ] eligible for data extraction. We later combined these results with those from the ten reviews initially used in the feasibility study so that we had a total of 43 reviews for analysis as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…After agreeing the seven inclusion criteria, a further 48 qualitative reviews were then identified from DARE and assessed. At this stage, 15 [ 20 34 ] were excluded as they failed one or more of the criteria, leaving us with 33 reviews [ 11 , 35 47 , 48 66 ] eligible for data extraction. We later combined these results with those from the ten reviews initially used in the feasibility study so that we had a total of 43 reviews for analysis as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Psychosocial adaptation has been explicitly or implicitly described as: ‘a process of change’ (Abad‐Corpa et al . , p. 3165, Brands et al . , p. 843).…”
Section: Resultsmentioning
confidence: 99%
“…The dynamic interplay between psychological processes of ‘gains’ and ‘losses’ has been highlighted in studies of older people's adaptation to dependency (Abad‐Corpa et al . ) or ‘healthy’ transitions in the lives of older people more broadly (Schumacher et al . ).…”
Section: Discussionmentioning
confidence: 99%